Corporate management structure of large Malaysian construction companies. - Adnan, Hamimah; Jusoff, Kamaruzaman (Macrothink Institute, 2009)
Corporate management structure is crucial for the understanding of corporate governance. Companies will have their own structure of corporate management. The environment and their planning and control mode will have an impact on way they do things daily, monthly and yearly. Learning the structure that suited most for different types of organisation would then be important and fruitful for any part that are related or affected by it. The aim of this study is to explore the parent company of large construction companies managing their local subsidiaries in Malaysia. This study is based on survey of the Malaysian contractors and aims to identify the corporate management structure in the Malaysian construction industry. The study found that construction firm need to develop a long-term vision of its strategic intent and need to upgrade productivity and have new technology. Parent companies need to maintain quality products to clients to projecting sound track record. Construction companies need o provide quality services to meet their client’s in formulation and implementing corporate strategies and business plan. They need to explore new construction technology to have competitive the edge in the market and they have to expand for regional expansion for higher business growth and synergies diversification to broaden revenue source, marketing plan and expand overseas markets.